Annao Pingchong decoction alleviate the neurological impairment by attenuating neuroinflammation and apoptosis in intracerebral hemorrhage rats. (28th June 2023) - Guo, Chun; Zhou, Xuqing; Wang, Xu; Wang, Haojie; Liu, Jian; Wang, Jinxi; Lin, Xiaoyuan; Lei, Shihui; Yang, Yi; Liu, Kai; Long, Hongping; Zhou, Desheng
Abstract: Ethnopharmacological relevance: Intracerebral hemorrhage (ICH) is a central nervous system disease that causes severe disability or death. Even though Annao Pingchong decoction (ANPCD), a traditional Chinese decoction, has been used clinically to treat ICH in China, its molecular mechanism remains unclear. Aim of the study: To study whether the neuroprotective effect of ANPCD on ICH rats is achieved by alleviating neuroinflammation. This paper mainly explored whether inflammation-related signaling pathways (HMGB1/TLR4/NF-κB P65) plays a role in ANPCD treatment of ICH rats. Materials and methods: Liquid chromatography-tandem mass spectrometry was used to analyze the chemical composition of ANPCD. ICH models were established by injecting autologous whole blood into the left caudate nucleus of Sprague-Dawley (SD) rats. Modified neurological severity scoring (mNSS) was used to assess the neurological deficits. The levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 were analyzed using enzyme-linked immunosorbent assay (ELISA). Pathological changes in the rat brains were observed using hematoxylin-eosin, Nissl, and TUNEL staining. The protein levels of HMGB1, TLR4, NF-κB p65, B-cell lymphoma 2 (Bcl-2), and Bcl-2-associated X protein (Bax) were measured by western blotting and immunofluorescence analysis. Results: Ninety-three ANPCD compounds were identified, including 48 active plasma components. Treatment with ANPCD effectively improved the outcome, as observed by the neurological function scores analysis and brain histopathology. Our results showed that ANPCD exerts its anti-inflammatory effects by significantly downregulating the expression of HMGB1, TLR4, NF-κB p65, TNF-α, IL-1β, and IL-6. ANPCD also exerted anti-apoptotic effects by significantly decreasing the apoptosis rate and Bax/Bcl-2 ratio. Conclusion: We found that ANPCD had neuroprotective effect in clinical work. Here, we also found that the action mechanism of ANPCD might be related to attenuate neuroinflammation and apoptosis. These effects were achieved by inhibiting the expression of HMGB1, TLR4 and NF-κB p65. Graphical abstract: Image 1 Highlights: ANPCD can alleviate the neurological impairment after ICH in Rats. ANPCD can attenuate neuroinflammation and apoptosis. ANPCD can decrease the expression of HMGB1, TLR4 and NF-κB p65.